Fitts’ Tapping Task as a New Test for Cognition and Manual Dexterity in Multiple Sclerosis: Validation Study - Glavor, Klaudia Duka; Weinstock-Guttman, Bianca; Vuletić, Gorka; Vranić Ivanac, Iva; Šimić, Nataša; Covey, Thomas J.; Jakimovski, Dejan (Medicina (Kaunas, Lithuania), 2022)
Introduction. Studies suggest that people with multiple sclerosis (pwMS) experience continuous and subclinical physical worsening, even as early as their disease diagnosis. Validating sensitive and reproducible tests that can capture subclinical disease activity early in the disease are clinically useful and highly warranted. We aimed at validating the utility of Fitts’ Tapping Task (FTT) as reproducible measure of psychomotor performance in pwMS. Materials and Methods. Thirty newly-diagnosed pwMS (within 2 years of diagnosis and Expanded Disability Status Scale; EDSS ≤ 2.0), 30 people with migraine (pwMig), and 30 healthy controls (HCs) underwent a psychomotor assessment using the FTT, O’Connor hand dexterity test, and Visual Reaction Time Test (VRTT). Hand strength was measured using a hand-grip dynamometer. Subjects also provided patient-reported outcomes (PROs) using the 36-Item Short Form Survey (SF-36). Intrarater and interrater reproducibility was acquired on 5 HCs by two independent operators. Test–retest reproducibility was determined in 5 pwMS over a 1-week follow-up. Eight pwMS returned for the same test procedures 2 years after the baseline assessment. Bland–Altman plots were used to determine the minimally detectable change (MDC) and logistic regression models determined the ability to differentiate between newly-diagnosed pwMS and HCs. Results. FTT exhibited a high intrarater and interrater reproducibility (interclass correlation coefficient of 0.961, p < 0.001). The test–retest demonstrated an MDC of the average FTT at > 15%. PwMS had significantly a slower FTT time and O’Connor dexterity time when compared to pwMig and HCs (p < 0.001 for both). Higher Fitts’ difficulty levels (4th and 6th difficulty) and average performance on the O’Connor test were able to differentiate newly-diagnosed pwMS from HCs with 80% accuracy (p < 0.01). Slower FTT performance was correlated with worse PROs due to physical health. Over the 2-year follow-up, and despite being clinically stable (no change in EDSS), 6 out of 8 (75%) pwMS had more than a 15% worsening in their average FTT time. Conclusions. FTT is a highly-reproducible test for measuring psychomotor performance in newly-diagnosed pwMS. FTT can capture insidious worsening in psychomotor performance and cognitive function in early stages of MS.